Screening and grading of brinjal (Solanum melongena) accessions for resistance to spotted beetle (Henosepilachna vigintioctopunctata) - RAJENDRAN, B; GOPALAN, M (The Indian Journal of Agricultural Sciences, 2013)
Brinjal or egg plant (Solanum melongena L.) is attacked by the spotted leaf beetle (Henosepilachna vigintioctoPunctata Fab : Coccinellidae : Coleoptera). Both adults and larvae feed on the leaves and under severe epidemic, the crop yield is highly reduced (Krishnamurti and Appana 1951). It is also polyphagus on hosts like potato (Solanum tuberosum L.), tomato (Lycopersicon esculentum Mill) and bittergourd (Momordica charantia L.) (Rajagopalan and Trivedi 1989). Since insecticide asage is highly disfavoured in egg plant, alternatively identifying resistance for spotted beetle was attempted earlier (Sambandam et al. 1972). Screening method involving in vitro method was utilized by Natarajan (1971). The mean leaf-area fed by known number of beetles for specific period was taken as a basis for evaluating the entries earlier. In this method, the intensity of leaf -damage was alone taken as the criterion for grading and the percentage incidence of damage under field conditions was not taken into account. The number of leaves affected in a plant also contributed towards yield potential of the plant. Hence in the present method, both the incidence (percentage of leaves affected) under field conditions and intensity (leaf area damage/unit time) were assessed and damage index computed for grading of resistance.